Narrowband aperiodic multilayers with flat spectral response for plasma diagnostics. (November 2022) - Yang, Zehua; Zhu, Jingtao; Zhu, Yunping; Li, Zhongliang; Luo, Hongxin; Si, Shangyu; Zhao, Li
Abstract: Aperiodic W/Si multilayer mirrors with the narrow bandwidth and the flat spectral response are presented as X-ray reflectors operated at 8.05 keV for plasma diagnostics. In this manuscript, aperiodic W/Si samples with different periods and thickness ranges were prepared on ultra-smooth silicon (100) substrates by direct-current magnetron sputtering. Grazing incidence X-ray reflection measurements were conducted to characterize the thickness distribution and the interfacial width of multilayer samples. Depth profiles of major elements in a periodic multilayer were investigated using time-of-flight secondary ion mass spectrometry to qualitatively estimate the effect of impurities from the residual gas. Cross-sectional transmission electron microscope images of the aperiodic multilayer indicate the asymmetric interfaces with the increasing interfacial width. The cumulative roughness model and the diffusion layer model were employed to fit the thickness sequence, interfacial roughness and diffusion zone width from GIXRR curves for further optimization with the given interfacial effect. The reflection spectrum of the optimal W/Si sample was measured at the beamline BL09B of Shanghai Synchrotron Radiation Facility. The measured results of the aperiodic W/Si multilayer exhibit the (56.2 ± 1.3)% reflectivity, 936eV bandwidth and 581eV flat-band region. Highlights: An aperiodic multilayer mirror operated at Cu-Kα line with a narrow bandwidth and a flat-band response was developed. A cumulative roughness model and a diffusion layer model were used to fit thickness array and interfacial structures. An optimized design with the given diffusion zones and roughness was conducted for improving spectral response. Spectral curve of the optimal sample shows (56.2 ± 1.3) % reflectivity, 936eV bandwidth and 581eV flat-band region.